Sodium Hypochlorite-induced Facial Hematoma Following Root Canal Treatment - Tribovane, Denil; Tortajada Bustelo , Juan Carlos; Rovira, Àlex (Iranian Endodontic Journal, 2024)
This case report highlights a rare complication of root canal treatment involving the inadvertent extrusion of sodium hypochlorite solution, resulting in a sodium hypochlorite-induced facial hematoma. A 44-year-old female patient presented significant right hemifacial swelling and ecchymosis following root canal therapy. Computed tomography imaging confirmed a hematoma involving the facial region without active signs of bleeding. Sodium hypochlorite, a potent cytotoxic agent commonly used in root canal procedures, was identified as the causative agent. Treatment consisted of prednisone, antibiotics, and NSAIDs, resulting in gradual improvement over a month. The cytotoxic properties of sodium hypochlorite, its variable concentrations, and risk factors associated with facial hematomas are discussed. It is essential to emphasize the rarity of such hematomas and highlight the need for precise technique, vigilant monitoring, and interdisciplinary collaboration to mitigate risks and prioritize patient safety.